Cytotoxic effect of γ-sitosterol from Kejibeling (Strobilanthes crispus) and its mechanism of action towards c-myc gene expression and apoptotic pathway (Medical Journal of Indonesia, 2014)
Background: This study aimed to analyze the cytotoxicity effect of γ-sitosterol isolated from "Kejibeling" (Strobilanthes crispus), a medicinal plant, on several cancer cell lines. The mechanisms of the effects were studied through the expression of cancer-caused gene, c-myc and apoptotic pathways. Methods: This in vitro study was done using human colon cancer cell lines (Caco-2), liver cancer cell lines (HepG2), hormone-dependent breast cancer cell lines (MCF-7) and the normal liver cell lines (Chang Liver). The cytotoxic effect was measured through MTT assay and the potential cytotoxic value was calculated by determining the toxic concentration which may kill up to 50% of the total cell used (IC50). Meanwhile, the cytotoxic mechanism was studied by determining the effect of adding γ-sitosterol to the c-myc gene expression by reverse transciptase-polymerase chain reaction (RT-PCR). The effect of Î³-sitosterol through apoptotic pathway was studied by using terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. Results: γ-sitosterol was cytotoxic against Caco-2, HepG2, and MCF-7 with IC50-values of 8.3, 21.8, and 28.8 μg/mL, respectively. There were no IC50-values obtained from this compound against Chang Liver cell line. This compound induced apotosis on Caco-2 and HepG2 cell lines and suppressed the c-myc genes expression in both cells. Conclusion: γ-sitosterol was cytotoxic against colon and liver cancer cell lines and the effect was mediated by down-regulation of c-myc expression and induction of the apoptotic pathways.